Birth Weight and Cognitive Development during Childhood: Evidence from India - Santosh Kumar; Kaushalendra Kumar; Ramanan Laxminarayan; Arindam Nandi (Global Labor Organization (GLO), 2019)
Health at birth is an important indicator of human capital development over the life course. This paper uses longitudinal data from the Young Lives survey and employs instrumental variable regression models to estimate the effect of birth weight on cognitive development during childhood in India. We find that a 10 percent increase in birth weight increases cognitive test score by 8.1 percent or 0.11 standard deviations at ages 5-8 years. Low birth weight infants experienced a lower test score compared with normal birth weight infants. The positive effect of birth weight on a cognitive test score is larger for boys, children from rural or poor households, and those with less-educated mothers. Our findings suggest that health policies designed to improve birth weight could improve human capital in resource-poor settings.
Keywords: I12; I15; I18; J13; J24; O12; 330; Birth weight; Test score; Cognition; PPVT; Children; Instrumental variable; India